Examining the emergence of digital society and the digital divide in India: A comparative evaluation between urban and rural areas - Laskar, Mahmudul Hasan (Frontiers in Sociology, 2023)
Digital society today is a central entity for transformation in society as well as a new methodological framework in interdisciplinary research. Digital society emerged as parallel to conventional society. An individual is not just a member of society but simultaneously a member of a digital society. Human beings are so inevitably engrossed in digital society that without its connections, their membership in real society stands meaningless. Digital technology is instrumental in social transformations in the realms of economy, polity, culture, and religion. The striking feature of digital society is digital data production in the form of big data. Unless conventional society, people’s every move and act in digital society are calculated and recorded as data. In this global context of digital society, India has opened opportunities for digitalization for its people in the year 2015-2016 though the process has been going on since 2000. Reliance Jio, a telecom company instituted the process at a larger level or mass scale through free unlimited internet packages. Soon India gained success in a momentum shift towards digital technologies. Service industries tremendously uplifted and new sectors came up; also, there emerged a digital revolution in all the conventional systems of economic, political, cultural, educational, religious, and legal spheres of society. Despite that, a serious issue sprouted, it is the digital divide or digital inequalities that cannot be overlooked or undermined in sociological study. It would be wrong to consider digital inequality as merely a technological division; we simply cannot isolate the issue into the technological term. There are some prevailing conditions determining digital inequalities. These conditions are socio-economic disparity and capability inequality. The study revealed that India’s prevailing socio-economic divide is the source of a wide digital divide in India. Digital divide exists in the educational and economic aspects of both rural and urban areas. Digital divide is also found between slum and affluent residential areas. The theoretical formulation of the study is based on Manuel Castell’s (2005, 2010) information society and Dijk’s (2006) Network society.